Peningkatan Aktivitas dan Hasil Belajar Siswa SD Melalui Media Game Edukasi Andorid - Rokhmatul Alfiah; Mohammad Faizal Amir (Jurnal Pendidikan Edutama, 2022)
Abstract: The low level of activity and learning outcomes on flat-shaped materials requires an appropriate solution, especially elementary school mathematics learning that is currently taking place during the COVID-19 pandemic. This study aims to increase the activity and learning outcomes of elementary school students on flat-shaped materials through the application of android educational game media. This media was created through the 1st and 2nd Math android application. The research method used is classroom action research with Kurt Lewin's model. This study lasted for two cycles with indicators of success, namely completeness of activities and student learning outcomes are at least 75% classically. The results showed that students' learning activities in the pre-cycle were 15% (less), the first cycle increased by 51.25%, and the second cycle was 82.75% (good). The increase in student learning outcomes in the pre-cycle was 41.25% (less), the first cycle increased by 66.75% (less), and the second cycle increased by 86% (good). Thus, the use of android educational game media improves elementary school students' activity and learning outcomes in flat-shaped material.Keywords: Activities, learning outcomes, educational game media, android technology Abstrak: Rendahnya aktivitas dan hasil belajar pada materi bangun datar membutuhkan suatu solusi yang tepat, terlebih pembelajaran matematika sekolah dasar yang dilakukan saat ini berlangsung selama masa pandemi covid-19. Tujuan penelitian ini adalah meningkatkan aktivitas dan hasil belajar siswa sekolah dasar pada materi bangun datar melalui penerapan media game edukasi android. Media ini dibuat melalui aplikasi android 1st and 2nd Math. Metode penelitian yang digunakan adalah penelitian tindakan kelas dengan model Kurt Lewin. Penelitian ini berlangsung selama 2 siklus dengan indicator keberhasilan yaitu ketuntasan aktivitas dan hasil belajar siswa berada minimal 75% secara klasikan. Hasil penelitian menunjukkan aktifitas belajar siswa pada prasiklus sebesar 15% (kurang), siklus I meningkat sebesar 51,25%, dan siklus II sebesar 82,75% (baik). Peningkatan hasil belajar siswa pada prasiklus sebesar 41,25% (kurang), siklus 1 meningkat sebesar 66,75% (kurang), dan siklus II  meningkat sebesar 86% (baik). Dengan demikian, penerapan media game edukasi android meningkatkan aktivitas dan hasil belajar pada materi bangun datar siswa sekolah dasar.Kata Kunci: Aktivitas, hasil belajar, media game edukasi, teknologi andorid